Silver Nanoparticles Biofabricated from Cinnamomum zeylanicum Reduce IL-6, IL-18, and TNF-ɑ in Female Rats with Polycystic Ovarian Syndrome - Shukrya H. Alwan; Mina H. AL-Saeed (International Journal of Fertility and Sterility, 2023)
Polycystic ovarian, or stein leventhal, syndrome (PCOS) is an inflammatory disorder resulting in metabolic dysregulation and ovarian dysfunction as well as women’s infertility. Management of PCOS requires multiple approaches. This experimental study was sought to assess the influence of Cinnamomum zeylanicum (CZ) derived silver particles (AgNPs) on inflammatory cytokines in rats with PCOS.In this experimental study, AgNPs were synthesized using CZ bark extract, and characterized by the scanning electron microscope (SEM) and atomic force microscope (AFM). Thirty female rats, rattus norvegicus, were grouped into five groups (6 animals/group). The experimental groups were vehicle control group (received 0.2 ml corn oil only), PCOS (received estradiol valerate of 4 mg/kg only), PCOS group received CZ extract (200 mg/kg), PCOS group received metformin (50 mg/kg) and PCOS group received AgNPs (3.53 mg/kg). After 30 days of treatment, serum concentrations of tumor necrosis factor-alpha (TNF-α), interleukins-18 (IL-18), and 6 (IL-6) were measured using ELISA.Significant elevation (P<0.05) was noted in TNF-α, IL-6, and IL-18 levels of the PCOS group when compared with findings in the control group (TNF-α: 250.4 ± 32.5 vs. 164.3 ± 34.4 ng/L, IL-6: 169.8 ± 9.4 vs. 77.0 ± 9.3 pg/ml, and IL-18: 45.9 ± 5.5 vs. 35.3 ± 4.1 ng/L). Importantly, AgNPs decreased all three inflammatory biomarkers in the treated group when compared with the PCOS group (TNF-α: 173.9 ± 31.2 vs. 250.4 ± 32.5 ng/L, IL-6: 133.7 ± 9.3 vs. 169.8 ± 9.4 pg/ml, and IL-18: 36.1 ± 6.2 vs. 45.9 ± 5.5 ng/L).CZ-derived AgNPs may have an anti-inflammatory effect in PCOS rats by decreasing the concentrations of inflammatory cytokines TNF-α, IL-6 and IL-18.